Latino small businesses in northwest Washington: Perceptions, challenges, and needs. Issue 3 (27th May 2017) - García-Pabón, José; Klima, Kenneth
Abstract: Despite the increase of Latino small businesses, they fail at a higher rate than their mainstream counterparts. Further, researchers and practitioners show insufficient understanding of Latino small businesses, over-relying on ethnic and nationality entrepreneurship that underestimate gender, education, and socioeconomic status. A responding framework maintains that structural forces push Latino immigrants into entrepreneurship because no other income opportunities are available to them. Considering both frameworks, we surveyed 82 Latino-owned businesses and conducted three focus groups in Washington State. We learnt that most (1) want a financially stable business, (2) are interested in talking with a business advisor, (3) lack a business plan, (4) use English and Spanish for business, (5) need help with paperwork for a loan, and (6) need computer training. We found too that business satisfaction derives from the emotional rewards and sense of accomplishment business owners felt in doing good work, helping others, and having financial success.